Evaluating the Impact of Whatsapp Media Intensity on Elementary Students' Self-Efficacy Growth - Irfan, Muhammad; Yusuf, Faidah (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to evaluate the impact of WhatsApp media intensity on the growth of elementary school students' self-efficacy. In the context of the current digital era, the use of social media such as WhatsApp has become an integral part of daily life, including in educational contexts. However, there is still a lack of understanding of how intensive WhatsApp use can affect the development of students' self-efficacy at the elementary school level. This research method employs a quantitative approach using questionnaires to collect data from 90 samples of elementary school students who actively use WhatsApp. The data is then statistically analyzed to evaluate the relationship between WhatsApp usage intensity and students' self-efficacy growth. The findings of this study indicate that WhatsApp media intensity has a significant impact on the growth of elementary school students' self-efficacy. These findings underscore the importance of paying attention to social media use in educational contexts, as well as the practical implications for designing more effective learning strategies in the current digital era. In conclusion, this research provides valuable insights into the role of WhatsApp media in enhancing elementary school students' self-efficacy and highlights the importance of integrating technology in educational contexts to support holistic student development..